Creating quaternary centers with high exo stereoselectivity using activated alpha-alkynyl dienophiles - Min, Sun-Joon; Jones, Gavin O.; Houk, K. N.; Danishefsky, Samuel J. (AMER CHEMICAL SOC, 2007)
Ethynyl substituents were used to direct a highly exoselective creation of quaternary carbon centers in Diels-Alder cycloaddition reactions involving activated alpha-alkynyl dienophiles. The origins of electronic activation and the high stereoselectivities of these reactions were investigated by the B3LYP density functional method.
Keywords: DIELS-ALDER REACTIONS; SECONDARY ORBITAL INTERACTIONS; VIBRATIONAL ABSORPTION; STEREOGENIC CENTERS; PAECILOMYCINE-A; ACIDITY TRENDS; DENSITY; STEREOCENTERS